2021
DOI: 10.1186/s12889-021-11059-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of and barriers to thalassemia screening in migrant populations: a cross-sectional study of Myanmar and Cambodian migrants in Thailand

Abstract: Background Thalassemia, an inherited hemoglobin disorder, has become a global public health problem due to population migration. Evidence-based strategies for thalassemia prevention in migrants are lacking. We characterized barriers to thalassemia screening and the burden of thalassemia in migrant workers in Thailand. Methods Multilingual demographic and KAP surveys were completed by 197 Thai, 119 Myanmar, and 176 Cambodian adults residing in Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…22 Funded by international health agencies, diagnostic services have been disseminated considerably in low-income countries. 23 However, an increasing trend in the mortality rate of thalassemia emerged after 2010. Challenges in the prevention and control of thalassemia must be addressed, including the cross-regional spread of migration and changes in the epidemiology of hemoglobinopathies, which may weaken prevention efforts in the 21st century.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Funded by international health agencies, diagnostic services have been disseminated considerably in low-income countries. 23 However, an increasing trend in the mortality rate of thalassemia emerged after 2010. Challenges in the prevention and control of thalassemia must be addressed, including the cross-regional spread of migration and changes in the epidemiology of hemoglobinopathies, which may weaken prevention efforts in the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing trend in the mortality rate of thalassemia emerged after 2010. Challenges in the prevention and control of thalassemia must be addressed, including the cross‐regional spread of migration and changes in the epidemiology of hemoglobinopathies, which may weaken prevention efforts in the 21st century 24 . Additionally, cultural, social, and ethical factors have been found to impact the effectiveness of early thalassemia screening 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is typically considered the consequence of dropping out, but it could also be attributed to the more personal intrinsic characteristics and their family financial situation which cause them to make their own decision to drop out. Mostly, the dropouts emigrated to Thailand working as workers with poor knowledge (Xu et al 2021), mostly employed in farms in the northeast region in Thailand (W. Kongnoo, et al, 2014) or worked at the garment factories where the expected wage is USD 177 per month (Finster 2015), increasing to USD 200 per month (Raksa Chan 2022) The minimum wage standard only applies to the textile, garment, and footwear industries for 80 percent of 3037 women over the ages of 24 with primary or secondary education (Edward et al 2020), many young people continue to be engaged in self-employment or unpaid family work (McKay, Mussida, and Veruete 2018). However, the limitation of this research is that it focuses mainly on the high school dropout rate in Battambang province, drawing warranted findings from some sufficient former researchers as secondary data.…”
Section: Literaturementioning
confidence: 99%
“…Studies [13,29,40,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] explored determinants of health coverage openly, whereas the authors of studies [27,31,44,49,51,[78][79][80] directly aimed to identify barriers and/or facilitators and studies [66,[81][82][83][84] coping strategies related to coverage.…”
Section: Determinants Barriers and Facilitators To Health Coveragementioning
confidence: 99%
“…Accordingly, low-cost or free of charge services were identified as facilitators [13,60,82]. Studies also found that lack of health information or health system understanding as well as poor health-literacy reduced access to health care [17,27,31,39,44,55,[66][67][68]78,80,81,83,84,91,95,105,109,110]. Complementary, information, staff communication, knowledge and perceived risk as well as school and health education were stated to increase access [16,51,69,100].…”
Section: Accessibilitymentioning
confidence: 99%